Presence of multiple HIV subtypes and a high frequency of subtype chimeric viruses in heterosexually infected women. - Iversen, A; Learn, G; Fugger, L; Gerstoft, J; Mullins, J; Skinhoj, P (1999)
The HIV-1 subtype distribution was determined in 41 HIV-positive women (-8% of all HIV-infected women in Denmark) belonging to different risk groups. HIV p17 gag and env gene subtypes were determined by DNA sequence analysis. Five different HIV subtypes were detected across all patients. Most HIV-1-positive women of Danish origin carried subtype B viruses, and a minority had virus belonging to subtypes A or C. All injecting drug users (IDUs) were infected with HIV subtype B viruses, whereas all non-B subtypes were present in cases linked to heterosexual transmission. In contrast, all women of African origin carried non-B HIV subtypes (subtypes A, C, D, or G) regardless of transmission mode. Of these women, 21% infected with non-B HIV subtypes appeared to be infected by subtype chimeric viruses and 7% were jointly infected with viruses belonging to two different subtypes (A and C). Data demonstrate a preferential representation of non-B HIV subtypes in women infected through heterosexual contact, as well as a high degree of recombination between viruses derived from endemic areas in which several HIV subtypes predominate. Combined with the increased incidence of heterosexual transmission of HIV, the results imply that an increased subtype diversity can be anticipated in newly infected individuals.